PENERAPAN ISO 45001:2018 MENGGUNAKAN ANALISIS GAP : (Studi pada Klausul 5, 9, dan 10 di PT Tri Ratna Diesel Lamongan) - Widiyanza Luthfi Yania; Winarko; Sahabat Sutanto (Poltekkes Kemenkes Surabaya, 2022)
PT Tri Ratna Diesel Lamongan is a pioneer company in Indonesia that produces various types of ships. Activities of the company can lead to various risks such as accidents and occupational disease, regarding that issue, the company needs to implement occupational health and safety management system that has been known globally. Therefore, PT. Tri Ratna Diesel implements ISO 45001:2018 to create safe and healthy working conditions for all workers. This study aimed to determine the quality of the OHS management system based on ISO 45001:2018 implemented at PT. Tri Ratna Diesel Lamongan. This research used a descriptive research method with a cross-sectional approach. Data were collected by interviews and observations. Interviews were conducted with the persons in charge of the OH&S section and the public relations section. The analysis was used to determine the quality of ISO 45001:2018 at PT. Tri Ratna Diesel Lamongan was gap analysis. The result of the assessment implementation of ISO 45001:2018 used gap analysis showed that the percentage of assessment in clause 5 about leadership and work participation was 93.75% (good), clause 9 about performance evaluation was 92.30% (good), clause 10 about continuous improvement was 100% (very good). These results indicate that the requirements and procedures of ISO 45001: 2018 have been implemented and well documented. PT. Tri Ratna Diesel Lamongan is advised to conduct a review process of the improvement recommendations that have been given and adjust them to the situation and condition of the company. The review process can be carried out to adjust to each department’s views in PT. Tri Ratna Diesel.